2014
DOI: 10.18553/jmcp.2014.20.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Association of Copayment with Likelihood and Level of Adherence in New Users of Statins: A Retrospective Cohort Study

Abstract: BACKGROUND: Statins remain a fundamental component of pharmacologic therapy for hyperlipidemia. Health benefits of statin therapy are jeopardized when adherence is reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…The Patient Protection and Affordable Care Act of 2010 (ACA) required that private insurers provide first-dollar coverage for services and medications with an "A" or "B" grade from the USPSTF without cost-sharing for primary prevention. [43][44][45] Some insurers responded by reducing the out-of-pocket costs for certain generic statins to zero regardless of indication. 46 Lower out-ofpocket costs have been associated with increased prescription fills for and adherence to statin ther- apy, 43,47 which have been subsequently associated with a reduction in rates of major cardiovascular events among those with a prior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The Patient Protection and Affordable Care Act of 2010 (ACA) required that private insurers provide first-dollar coverage for services and medications with an "A" or "B" grade from the USPSTF without cost-sharing for primary prevention. [43][44][45] Some insurers responded by reducing the out-of-pocket costs for certain generic statins to zero regardless of indication. 46 Lower out-ofpocket costs have been associated with increased prescription fills for and adherence to statin ther- apy, 43,47 which have been subsequently associated with a reduction in rates of major cardiovascular events among those with a prior myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Watanabe and colleagues reported that among new statin users, patients who did not pay out-of-pocket costs had a nearly 20 % increased odds of compliance (MPR ≥ 0.80) relative to patients with any out-of-pocket costs. 5 Although patients saved an average of $20 per 30-day supply of statin therapy, we have previously shown that this cohort of switchers is as compliant as patients who remain on branded statins. 28 Importantly, while patients who switched had marked reductions in statin costs, savings for all medication regimens were on average only $5 per month and may not have been large enough to influence compliance.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies have shown that lower prescription copayments correlate with better compliance with statin therapy. [2][3][4][5]27 However, to our knowledge, these studies were not conducted in populations switching from branded to generic agents. For example, Watanabe and colleagues reported that among new statin users, patients who did not pay out-of-pocket costs had a nearly 20 % increased odds of compliance (MPR ≥ 0.80) relative to patients with any out-of-pocket costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Eaddy et al59 summarized additional strong evidence that even very low copays of US $3–US $5 per prescription may strongly deter adherence in low-income populations. Most recently, Watanabe et al60 determined that statin adherence among the Veterans Affairs population was higher among those without out-of-pocket expenses; however, adherence dropped in cases where statins required a copayment, but other medications were free, suggesting the importance of the relative cost of medications for those on a multiple-drug regimen. Additionally, results from the MI FREEE Trial61 suggested that eliminating copayments for statins could also improve adherence following a defined cardiac event.…”
Section: Intervention Strategiesmentioning
confidence: 99%